POSTMODERN INDO-ANGLIAN LITERATURE: EXPLORING THE INDIGENOUS PERSPECTIVE - Dr. Surender Singh (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Postmodern Indo-Anglian literature offers a rich tapestry of narratives that reflect the complexities and multiplicities of Indian identities and experiences. This body of literature, emerging prominently in the late 20th and early 21st centuries, intertwines indigenous cultural elements with global literary techniques, thereby providing a unique lens through which to explore Indian society, history, and politics. By employing postmodern strategies such as metafiction, intertextuality, and fragmentation, Indo-Anglian writers challenge traditional narratives and offer alternative perspectives that highlight the diversity and dynamism of India's cultural landscape. Key themes include the deconstruction of colonial legacies, the interrogation of modernity, and the celebration of hybridity and plurality. Authors like Salman Rushdie, Arundhati Roy, and Amitav Ghosh, among others, delve into the indigenous perspective, reclaiming and redefining Indian identity in a globalized world. This abstract underscore the significance of postmodern Indo-Anglian literature in contributing to global literary discourse and enriching our understanding of India's multifaceted heritage.